PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS CORE (CONNECTING, ORGANIZING, EXTENDING, DAN REFLECTING) MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL - Zamzam, Kenys Fadhilah; Ndilu Hamandika, Orvinus (Universitas Insan Budi Utomo, 2022)
Student worksheets (LKS) are student guides in solving problems. LKS based on CORE (Connecting, Organizing, Extending, and Reflecting) on the material of a two-variable equation system had advantages in presenting the material and had an attractive appearance. The development model used ADDIE model. The subjects of this study were 20 students of SMAN 1 Nggaha Ori Angu. The data collection process used an instrument in the form of a validation sheet with the aim of measuring the validity of the LKS, post-test to determine student learning outcomes and student responses to the LKS developed to determine the effectiveness of the LKS. The results of data analysis showed that from the two validators the average value was 3.32 which showed the valid criteria. The percentage of students' average completeness score was 78%. Based on the established criteria, it can be said that students had good mastery of the SPLDV material. The student response questionnaire data obtained a percentage of 85.7%, so based on the criteria it was concluded that students showed a positive response to the developed LKS. Overall, the CORE-based LKS on SPLDV material was effectively used in the learning process.